Spatial Microstructural Ordering of Expansive Clay Minerals - T. López-Lara; J. B. Hernández-Zaragoza; D. Carreón-Freyre; M. Cerca; E. Rojas-González; A. G. Minor Franco; G. Martínez-Barrera; R. Salgado-Delgado (Advances in Civil Engineering)
The volumetric change within soils containing expanding clays depends upon their spatial ordering and their mineralogy. So this work studies the spatial microstructural ordering and mineralogy of different expanding clays in order to correlate them with some of their geotechnical properties (plasticity, classification, and expansion). The clay microstructure was obtained using X-ray diffraction, and sweeping electronic microscopy. Physical characterization includes pH analysis. Clays with greater swelling (12.1–14.6% expansion) present greater agglomeration (gathering) (20–50 microns) in a flocculated structure that mainly contained sodic montmorillonite with 14–22 Å openings and 8.28 average pH, which indicates high electron concentrations with border-face interactions. Clays with the least expansion (7.6%) present lower agglomerations (5–10 microns) with face-to-face contacts within a dispersed structure that mainly contained calcium montmorillonite with openings lower than 15 Å and pH 7.56, which indicates a low electron concentration and face-to-face interaction. Major clay expansion corresponds to a greater size agglomerates, greater opening between particles, and greater pH presenting border-face and face-to-face interactions of a flocculent structure. Yet, the soils with lower expansion only present face-to-face interactions corresponding to a dispersed structure.